S.M. Medaglia, P. Radici, L. Rossetti, S. Sconocchia (eds.): Dizionario delle Scienze e delle Tecniche di Grecia e Roma, Pisa/Roma: Fabrizio Serra, 2 v., 2010, 1346 pp. - D'Alessandro, Antonietta (2012)
No presenta resumen